Bibliometric Analysis of Heterarchy: Toward a Paradigm Shift in Public Administration Studies - Kudus, Imanudin; Nurasa, Heru; Widianingsih, Ida; Karlina, Nina; Jawan, Jayum Anak (Universitas Padjadjaran, 2024)
The study of public administration developed from the Old Public Administration to the New Public Service, bringing management and public organizations to shift from the traditional paradigm to the modern paradigm. Organizations were originally seen as machines that emphasized hierarchy. The modern perspective states that hierarchy is no longer an effective organizational strategy. The new public administration steered organizations toward collaboration, consensus, and democratic management to encourage the development of a heterarchical approach. The research results were visualized using bibliographic research methodology and the VOSviewer program. Access Scopus database data using the following keywords, title-abs-key (